Prolonged insulin treatment sensitizes apoptosis pathways in pancreatic β cells. Issue 3 (September 2016) - Bucris, E; Beck, A; Boura-Halfon, S; Isaac, R; Vinik, Y; Rosenzweig, T; Sampson, S R; Zick, Y
Abstract : Insulin resistance results from impaired insulin signaling in target tissues that leads to increased levels of insulin required to control plasma glucose levels. The cycle of hyperglycemia and hyperinsulinemia eventually leads to pancreatic cell deterioration and death by a mechanism that is yet unclear. Insulin induces ROS formation in several cell types. Furthermore, death of pancreatic cells induced by oxidative stress could be potentiated by insulin. Here, we investigated the mechanism underlying this phenomenon. Experiments were done on pancreatic cell lines (Min-6, RINm, INS-1), isolated mouse and human islets, and on cell lines derived from nonpancreatic sources. Insulin (100nM) for 24h selectively increased the production of ROS in pancreatic cells and isolated pancreatic islets, but only slightly affected the expression of antioxidant enzymes. This was accompanied by a time- and dose-dependent decrease in cellular reducing power of pancreatic cells induced by insulin and altered expression of several ER stress response elements including a significant increase in Trb3 and a slight increase in iNos . The effect on iNos did not increase NO levels. Insulin also potentiated the decrease in cellular reducing power induced by H2 O2 but not cytokines. Insulin decreased the expression of MCL-1, an antiapoptotic protein of the BCL family, and induced a modest yet significant increase in caspase 3/7 activity. In accord with these findings, inhibition of caspase activity eliminated the ability of insulin to increase cell death. We conclude that prolonged elevated levels of insulin may prime apoptosis and cell death-inducing mechanisms as a result of oxidative stress in pancreatic cells.